Empowering women for conflict resolution: A case study on Laiya Island, Pangkep Regency, Indonesia - Dwia Aries Tina Pulubuhu; R. Rahmatia; Sherry Adelia; S. Seniwati (Journal of Community Service and Empowerment, 2023)
This study aimed to enhance public awareness regarding conflict identification and encourage the adoption of suitable resolution strategies. The community service initiative employed a training approach, engaging a group of 52 women on Laiya Island, Pangkep Regency, South Sulawesi, Indonesia. Furthermore, this activity was a collaboration between CPCD (Center for Peace, Conflict, and Democracy) Hasanuddin University and the Pangkep District Fisheries Service. The results showed that an effective measure for conflict prevention entailed the empowerment of women. Therefore, there had been a notable improvement in community understanding of appropriate conflict resolution techniques. This activity introduced a novel approach where the empowerment of women through the utilization of marine products and the establishment of micro, small, and medium enterprises (MSMEs) as well as home industries played a vital role in conflict resolution strategies. In conclusion, the conflicts experienced on Laiya Island were minimal, and the community successfully resolved disputes through meaningful discussions.